Evaluation of climate change impact on extreme temperature variability in the Blue Nile Basin, Ethiopia - M. A.-H. Mohamed (Geoscientific Instrumentation, Methods and Data Systems, 2021)
Climate change raises important issues concerning hydrological engineering. The impact of climate change on important river basins should be investigated rigorously. Extreme temperature variability has a direct impact on the hydrological cycle, especially the evaporation component. In this paper, spatial and temporal patterns of changes in extreme temperatures were investigated using 10 meteorological stations' data for the period 1950–2018 in the Blue Nile Basin. Long-term trends in the Blue Nile Basin annual and monthly temperatures were investigated. The statistical significance of the trend was calculated by applying the Mann–Kendall (MK) test. The analysis of data was performed using the coefficient of variance and anomaly index. The results showed that the annual maximum and minimum temperatures were increasing significantly with a magnitude of 0.037 and 0.025 ∘C per decade respectively in the period from 1950 to 2018. The result of the Mann–Kendall analysis test revealed a marked increase in the mean maximum and minimum temperature trends over time during the study period (the minimum temperature rate is more evident than the maximum). The long-term anomalies of mean annual minimum temperature revealed the interannual variability while the trend after 1977 was higher than the long-term average, which is proof of the warming trend's existence during the last two decades of the 20th century.